Discussion on Key Issue of Batch Testing About the Security of Mobile Application - Lihong Xue; Jingfang Zheng; Yongcheng Jiang; Weiqing Wang (Dianxin kexue)
Based on the service secure operating requirements for telecom carrier's mobile application store, the main problem of batch testing for the security of mobile application was analyzed and the architecture of batch testing was proposed. Then, the key issue about the architecture was discussed. Furthermore, some advices for the constructing of batch testing's service platform were given.